Pengaruh Model Pembelajaran Discovery Learning Tipe POE dan Aktivitas Belajar terhadap Kemampuan Metakognitif - Dwi Susanti; Chairul Anwar; Fredi Ganda Putra; Netriwati; Kiki Afandi; Santi Widyawati (Jurnal Inovasi Matematika, 2020)
Remembering formulas without understanding its concept is a constraint in students’ learning activities. Therefore, the learning model needs to be implemented to make students active in understanding the concept of the material that teachers provide. This research intention is to reveal: (1) the effect of the discovery learning model of POE learning type towards metacognitive ability; (2) the influence of learning activity towards metacognitive ability; (3) the interaction between discovery learning model of POE learning type and learning activity toward metacognitive ability. This research applied experimental research; it was conducted through experiments or trials. It used a Quasy-Experimental design that has control group design, but it does not fully function to control the external variables that affect the execution of the experiment. The research outcomes show: (1) there is an effect of discovery learning model of POE learning type towards metacognitive ability; (2) there is an influence of learning activity towards students’ metacognitive ability; (3) there is no interaction between discovery learning model of POE learning type and learning activity toward students’ metacognitive ability.